Jim Musco. - Hamilton, Dorothy, 1906-; Ponter, James J. (Scottdale, Pa., Herald Press, 1972)
A twelve-year-old Delaware Indian boy chooses to stay with his mother in Indiana instead of moving west with his tribe.
Keywords: Musco, Jim -- Juvenile fiction; Delaware Indians -- Fiction